Nonperturbative contribution to the strange-antistrange asymmetry of the nucleon sea; Physical Review D; Vol. 93, iss. 5 - Vega A. Alfredo; Schmidt I. Ivan; Gutsche Th. Thomas; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2016, 2016)
Title screen